Economic Diplomacy as a Pillar of Bilateral Engagement between Kenya and Uganda from 1962-2024 - Kenneth Kaunda Odulwa; Kizito Muchanga Lusambili; Josephat Nairutia Kemei (CV. AFDIFAL MAJU BERKAH, 2025)
This article underscored the economic diplomacy as a pillar of bilateral engagement between Kenya and Uganda from 1962-2024. This is due to the fact that, since the Kenya’s attainment of independence in 1963, and Uganda in 1962, a relationship that is not limited to cooperation, competition and mutual dependency has been going on. This article reviewed related literature and gaps identified. It adopted historical research design which enabled the study to relate the past events with the current. Administrative directors, diplomats, immigration agents, security guards, traders, and certain homeowners with land near the border were among the groups targeted. Since the study was qualitative in nature, it adopted purposive and snowballing techniques. The research found out that; both countries have utilized economic and peace diplomacy to strengthen ties, particularly in areas such as infrastructure development and cross-border trade. Notably, Uganda is Kenya's second-largest export destination, accounting for 9.5% of Kenya's total exports in 2023. Conversely, Kenya is a significant export partner for Uganda, representing 16.88% of Uganda's total exports. It also emerged that; In light of the fact that Uganda is a landlocked country and Kenya is dependent on the Ugandan market for the export of its produce, the diplomatic relations between Kenya and Uganda are of great significance. Additionally, the research recommends that; ultimately, a comprehensive approach that combines empirical data and interpretive insights is crucial for maximizing the benefits of economic diplomacy.